Ein Jahr DAX 40: Weitere Verbesserungen sind erforderlich - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2022)
– In the aftermath of the Wirecard scandal the German lead stock market index DAX has undergone a series of reforms, including the introduction of a profitability criterion based on EBITDA for new DAX members and enhanced financial reporting requirements with specified sanctions for non- compliance. Furthermore, DAX members need to adhere to certain provisions in the German Corporate Governance Code relating to audit committees. The final step of the reform was implemented in September 2021: the extension of the DAX from 30 to 40 constituents, with the ranking based solely on the free float market capitalisation. After one year of experience with the new design of the DAX, this paper concludes that the reform has strengthened the DAX in terms of diversification, quality and adaptability. However, there is still room for further improvement by introducing a minimum ESG score for DAX companies and thus making sustainability a relevant factor in the selection process. In addition, full compliance with the recommendations of the German Corporate Governance Code should be a condition for DAX companies. Furthermore, the profitability criterion should be applied on a continuous basis to ensure that loss-making companies can be excluded from the DAX after a grace period
urn:nbn:de:hebis:30:3-634429
Keywords: G1; G2; 330; DAX; Reform; Deutschland